KUALITAS PRODUK, PROMOSI DAN HARGA : PENGARUHNYA TERHADAP KEPUTUSAN PEMBELIAN PRODUK WARDAH PADA MAHASISWA ITB ASIA MALANG - Yesi Pramita; Ike Kusdyah Rachmawati; Mohammad Bukhori (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to analyze the influence of product quality, promotion and price on purchasing decisions of Wardah products among ITB ASIA Malang students. This type of research is a quantitative approach research. The population in this study were ITB Asia Malang students. The sample collection technique in this study was Purposive sampling. In this study, to determine the size of the research sample using the Slovin formula. In this study, the sample taken was 85 people. The questionnaire trial consisted of validity tests, reliability tests, classical assumption tests which included: normality tests, multicollinearity tests, heteroscedasticity tests, and there were F tests (simultaneous) and t tests (partial). The analysis technique in this study only used multiple linear regression analysis methods. The results showed that: product quality The product quality variable has a significant effect on purchasing decisions. The promotion variable has a significant effect on purchasing decisions. The price variable has a significant effect on purchasing decisions. The product quality and price variables together have an effect on purchasing decisions.